2017
DOI: 10.1016/j.tice.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Ecto-5′-nucleotidase (CD73) regulates bone formation and remodeling during intramembranous bone repair in aging mice

Abstract: Ecto-5′-nucleotidase (CD73) generates adenosine, an osteoblast activator and key regulator of skeletal growth. It is unknown, however, if CD73 regulates osteogenic differentiation during fracture healing in adulthood, and in particular how CD73 activity regulates intramembranous bone repair in the elderly by using a CD73 knock-out (CD73−/−) mouse model. Monocortical tibial defects were created in 46 to 52-week-old wild type (WT) and CD73−/− mice. Injury repair was analyzed at post-operative days 5, 7, 14 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 19 publications
0
13
0
1
Order By: Relevance
“…Although ALP and CD73 have never been associated together with osteogenic potential, singularly they were previously correlated with osteogenic differentiation. CD73 was shown to regulate bone formation and remodeling in intramembranous bone repair [ 48 ]. In our study, we demonstrated that CD73 expression levels inversely correlate with the osteogenic differentiation ability of 17 human AD-MSC primary preparations (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Although ALP and CD73 have never been associated together with osteogenic potential, singularly they were previously correlated with osteogenic differentiation. CD73 was shown to regulate bone formation and remodeling in intramembranous bone repair [ 48 ]. In our study, we demonstrated that CD73 expression levels inversely correlate with the osteogenic differentiation ability of 17 human AD-MSC primary preparations (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…CD73, ecto-5′-nucleotidase, is also a typical MSC marker, and induces bone formation via the synthesis of adenosine, an osteoblast activator and key regulator 20,21 . The CD73 inhibitor adenosine 5′-(α,β-methylene) diphosphate induces chondrogenic matrix deposition, but reduces mineral matrix deposition and the expression of osteogenic markers 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with mutations in the ADA gene and the consequent increase in adenosine availability, present radiological bone defect including scapular and ribs changes, alteration due to imbalance between osteoclasts and osteoblasts functions resulting in low bone formation (Cederbaum et al, 1976;Sauer et al, 2009;Manson et al, 2013). mRNA of CD39 and CD73 is expressed in precursor and mature osteoclasts and mice lacking CD73 have osteopenia associated with a higher number of osteoclasts compared to control mice and present a delay in bone regeneration due to an impairment in osteoblast activity (Takedachi et al, 2012;Bradaschia-Correa et al, 2017). Administration of Dipyridamole (440 mg/day), a drug that blocks adenosine re-uptake increasing its extracellular availability, was tested on RA patients and it has been shown that the drug does not raise blood purine levels and does not change patients symptoms .…”
Section: P1 Receptorsmentioning
confidence: 99%